Strategi Pendidikan Karakter Rasa Tanggung Jawab Peserta Didik Melalui Kegiatan Pramuka - Binti Sulyani (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
This research aims to describe the Character Education Strategy for a Sense of Responsibility for students. The method of this research is a qualitative approach. "The intended qualitative approach is a research process that uses scientific studies with the aim of interpreting the conditions currently occurring in the field." The data sources used in this research were obtained from people who supported them by providing information, namely from the Madrasah Head or Principal, class teachers, Scout Leaders and parents using observation, interviews and documentation techniques. The research data is then analyzed using data condensation, data display, and conclusion drawing/verification. The results obtained from this research are that to implement character education for a sense of responsibility, teachers and scout leaders use expository strategies or the same as Ki Hadjar Dewantara's learning concept, namely "ing ngarsa sung tuladha (in the front giving an example), ing madya mangun karsa (in the middle giving motivation), tut wuri handayani (behind giving encouragement)”. Habituation strategies and involving other people, including parents, are also used in implementing character education for a sense of responsibility.